Electrocatalytic multicomponent assembling of aminouracils, aldehydes and malononitrile: An efficient approach to 7-amino-pyrido[2,3-d]pyrimidine-6-carbonitrile derivatives - Kazemi-Rad Reyhaneh; Azizian Javad; Kefayati Hassan (Journal of the Serbian Chemical Society, 2016)
Electrocatalytic multicomponent transformation of 6-aminouracils, aromatic aldehydes and malononitrile in ethanol in an undivided cell in the presence of potassium bromide as an electrolyte leads to 7-amino-pyrido[2,3- d]pyrimidine-6-carbonitrile derivatives in short reaction times (8-20 min) and good to high yields (70-86%).